Hexamethylenetetramine crystal material and preparation method thereof
By preparing hexamethylenetetramine crystal materials, using their amino groups to react with carbon dioxide to fix CO2 in the compound, the problem of high temperature and long-term catalysis in the prior art is solved, and efficient carbon fixation is achieved at room temperature. And a new crystal material with good electrochemical properties was generated.
Patent Information
- Application Number
- CN202411653827.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art has a high temperature and long-term catalysis limitation in the CO2 carbon sequestration reaction, which leads to high energy consumption and safety risks. At the same time, it is unable to effectively utilize the ungenerated crystal materials in the mixed solution, resulting in waste of resources.
Hexamethylenetetramine crystal material, whose chemical formula is [C6H12N4][CH2O][K(H2O)]{[β-Mo8O26]0.5}, crystallized by evaporation of aqueous solution, and the material is prepared by using hexamethylene group. The amino group of tetramine reacts chemically with carbon dioxide to immobilize CO2 in the compound.
Carbon sequestration reaction is realized at room temperature, and the raw materials act as substrates and catalysts, which improve the reaction rate and carbon sequestration effect, and at the same time generate a new crystal material with good electrochemical properties.
Smart Images

Figure CN119504768A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and in particular relates to a hexamethylenetetramine crystal material and a preparation method thereof. Background Art
[0002] In the process of carbon cycle, biological carbon fixation plays a vital role. CO2 capture and utilization technology provides new possibilities for energy transformation and promotes sustainable development. Therefore, by converting CO2 into clean energy and other useful products, greenhouse gas emissions can be effectively reduced, thereby addressing the challenges of climate change and prompting people to find more effective and sustainable CO2 fixation and resource utilization technologies.
[0003] On the road to a sustainable low-carbon future, in addition to the physical capture and permanent underground deposition of anthropogenic CO2 emissions, another attractive method is to fix carbon by converting CO2 into value-added chemicals and reusable materials through catalytic chemical reactions. The corresponding target products are synthesized by hydrothermal method. Any crystalline material that does not form in the mixed solution will be abandoned, which is also a waste of resources. Moreover, most of the synthesis processes require high-temperature catalysis for a long time. In addition to consuming more energy in the process, the higher temperature also poses a safety hazard. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a hexamethylenetetramine crystal material and a preparation method thereof, so as to solve the technical problem of many restrictive conditions in carbon fixation reaction.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a hexamethylenetetramine crystal material, the chemical formula of which is [C6H 12 N4][CH2O][K(H2O)]{[β-Mo8O 26 ] 0.5}, the crystal material belongs to the triclinic system, the space group is P-1, and the unit cell parameters are α=97.344(10)°, β=101.117(9)°, γ=108.658(11)°,
[0006] The invention also discloses a method for preparing a hexamethylenetetramine crystal material, comprising the following steps: crystallizing hexamethylenetetramine (HMTA), cyanide and molybdenum oxide isopoly acid through evaporation reaction of an aqueous solution to obtain the hexamethylenetetramine crystal material.
[0007] Hexamethylenetetramine is attractive as a molecular scaffold with a high degree of symmetry and the presence of four equivalent hydrogen bond acceptor nitrogen atoms. In the pyrolysis or gasification process of biomass, it may help promote the reaction and promote the conversion of organic matter, thereby improving the carbon fixation effect. The hexamethylenetetramine and molybdenum oxide isopoly acid used in the present invention are both reaction substrates and catalysts to promote the reaction, fixing CO2 between the isopoly acid and the hexamethylenetetramine, forming a new carbon fixation mode.
[0008] On the basis of the above technical solution, the present invention can also be improved as follows:
[0009] Furthermore, the method comprises the following steps: dissolving hexamethylenetetramine, cyanide and molybdenum oxyisopoly acid respectively, then mixing them, allowing the mixture to react for 6-8 days, and obtaining a hexamethylenetetramine-type crystalline material after the solution is naturally evaporated to dryness; the molar ratio of hexamethylenetetramine, cyanide and molybdenum oxyisopoly acid is 1.3-1.5:5.5-5.8:1-1.5.
[0010] Furthermore, the cyanide is potassium thiocyanate (KSCN) or potassium cyanate (KOCN); the molybdenum oxoisopoly acid is ammonium molybdate ((NH4)2MoO4) or sodium molybdate (Na2MoO4).
[0011] The main group involved in the carbon fixation process in ammonium molybdate is the ammonium ion (NH4 + ), ammonium ions can act as a nitrogen source to react with carbon dioxide to form compounds such as ammonium carbonate, which can further promote the fixation of carbon dioxide.
[0012] Furthermore, hexamethylenetetramine and cyanide are first dissolved separately and then mixed to obtain a premixed solution, and then the premixed solution is added to the molybdenum oxide isopoly acid solution and mixed evenly to obtain a mixed solution.
[0013] Furthermore, the pH value of the molybdenum oxyisopolyacid solution is 1-1.5.
[0014] Furthermore, the reagent for adjusting the pH value is a hydrochloric acid, sulfuric acid or nitric acid solution with a concentration of 30-40wt%.
[0015] Furthermore, the static reaction time is 7 days.
[0016] Furthermore, the molar ratio of hexamethylenetetramine, cyanide and molybdenum oxyisopoly acid is 1.42:5.55:1.02.
[0017] The beneficial effects of the present invention are:
[0018] 1. The preparation process of the present invention can be carried out at room temperature, and the raw materials used not only participate in the reaction as substrates, but also act as catalysts to accelerate the reaction rate. The amino (-NH2) group in hexamethylenetetramine can participate in the carbon fixation reaction, especially in carbon capture and utilization, the amino group reacts chemically with carbon dioxide to form relatively stable ammonium carbonate or other carbon-containing compounds. This reaction is usually achieved through a nucleophilic reaction between the amino group and carbon dioxide, thereby fixing the carbon dioxide in the compound. Therefore, in the hexamethylenetetramine molecule, the four amino groups are the main active parts that participate in the carbon fixation process. Potassium ions themselves will not directly participate in the reaction with carbon dioxide, but in some cases, they can act as assisting ions of the catalyst in the reaction or improve the efficiency of the carbon fixation reaction by affecting the reaction conditions. The molybdenum ion (MoO4 2- ) can also act as a catalyst, promoting the reaction with carbon dioxide and producing a carbon fixation effect under normal CO2 concentrations.
[0019] 2. The present invention produces new crystal materials while absorbing CO2 in the air. The structure of the prepared hexamethylenetetramine crystal materials undergoes internal stretching vibration changes as the temperature changes, thereby affecting the change of the electrical properties of the crystal materials and greatly improving the Mo 6+ / Mo 4+ The reversibility of redox gives it good electrochemical properties and has good application prospects in electricity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a physical picture of the product obtained in Example 4;
[0021] Figure 2 is the infrared spectrum of hexamethylenetetramine;
[0022] Figure 3 This is the infrared spectrum of hexamethylenetetramine crystalline materials;
[0023] Figure 4 This is the XRD pattern of hexamethylenetetramine crystalline materials;
[0024] Figure 5 This is the structural unit diagram of hexamethylenetetramine crystalline materials at 100K;
[0025] Figure 6 This is the structural unit diagram of hexamethylenetetramine crystalline materials at 293K;
[0026] Figure 7 It is a one-dimensional chain structure diagram of hexamethylenetetramine crystal materials along the b-axis direction;
[0027] Figure 8It is a one-dimensional chain structure diagram of hexamethylenetetramine crystal materials along the a-axis direction;
[0028] Fig. 9 It is a two-dimensional network structure diagram of hexamethylenetetramine crystal materials along the b-axis direction;
[0029] Fig.10 It is a three-dimensional structure diagram of hexamethylenetetramine crystal materials along the b-axis direction;
[0030] Fig.11 It is the TGA-DTG curve of hexamethylenetetramine crystalline material;
[0031] Fig.12 It is the Hirshfeld surface diagram of hexamethylenetetramine crystal materials;
[0032] Fig.13 It is the H···H interaction fingerprint of hexamethylenetetramine-based crystal materials;
[0033] Fig.14 It is the H···O interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0034] Fig.15 It is the N···H interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0035] Fig.16 It is the H···N interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0036] Fig.17 It is the N···C interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0037] Fig.18 It is the C···C interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0038] Fig.19 It is the H···C interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0039] Fig. 20 It is the N···O interaction fingerprint of hexamethylenetetramine-based crystalline materials;
[0040] Fig.21 These are the cyclic voltammetry test results of hexamethylenetetramine crystalline materials. DETAILED DESCRIPTION
[0041] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
[0042] The hexamethylenetetramine (HMTA) used below was purchased from Hutubi Ruiyuantong Chemical Co., Ltd.; ammonium molybdate and sodium molybdate were purchased from Shanghai Qingxi Chemical Technology Co., Ltd.; potassium thiocyanide and potassium cyanate were purchased from Beijing Bailingwei Technology Co., Ltd.
[0043] Example 1
[0044] A method for preparing a hexamethylenetetramine crystalline material, the reaction equation is as follows:
[0045]
[0046] Specifically, the method comprises the following steps: firstly, 0.2 g (1.42 mmol) of hexamethylenetetramine and 0.55 g (5.55 mmol) of KSCN are dissolved in 5 mL of water respectively, and then mixed to obtain a premixed solution; 0.34 g (1.4 mmol) of Na2MoO4 is dissolved in 5 mL of water, and then 2 mL of 40 wt% nitric acid solution is added to make the pH value of the Na2MoO4 solution 1, and then the premixed solution is dripped into the Na2MoO4 solution and mixed evenly, and finally the mixed solution is allowed to stand for reaction for 8 days, and the hexamethylenetetramine crystalline material is obtained after the solution is naturally evaporated to dryness.
[0047] Example 2
[0048] A method for preparing a hexamethylenetetramine crystalline material, the reaction equation is as follows:
[0049]
[0050] Specifically, the method includes the following steps: first, 0.2 g (1.42 mmol) of hexamethylenetetramine and 0.57 g (5.79 mmol) of KOCN are dissolved in 5 mL of water respectively, and then mixed to obtain a premixed solution; 0.34 g (1.4 mmol) of Na2MoO4 is dissolved in 5 mL of water, and then 2 mL of a 30 wt% sulfuric acid solution is added to make the pH value of the Na2MoO4 solution 1.5, and then the premixed solution is dropped into the Na2MoO4 solution and mixed evenly, and finally the mixed solution is allowed to stand for 6 days to react, and the hexamethylenetetramine crystalline material is obtained after the solution is naturally evaporated.
[0051] Example 3
[0052] A method for preparing a hexamethylenetetramine crystalline material, the reaction equation is as follows:
[0053]
[0054] Specifically, the method includes the following steps: first, 0.2 g (1.42 mmol) of hexamethylenetetramine and 0.55 g (5.55 mmol) of KSCN are dissolved in 5 mL of water respectively, and then mixed to obtain a premixed solution; 0.27 g (1.02 mmol) of (NH4)2MoO4 is dissolved in 5 mL of water, and then 2 mL of 36.5 wt% hydrochloric acid solution is added to make the pH value of the (NH4)2MoO4 solution 1.2, and then the premixed solution is dropped into the (NH4)2MoO4 solution and mixed evenly, and finally the mixed solution is allowed to stand for 7 days to react, and a purple hexamethylenetetramine crystalline material is obtained after the solution is naturally evaporated.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 3 is that the molar ratio of the raw materials hexamethylenetetramine, KSCN and (NH4)2MoO4 is adjusted to 1:4:1, and the other implementation conditions are the same as those of embodiment 3. The results are as follows Figure 1 As shown, purple crystals are produced.
[0057] In order to preliminarily determine the main components of the purple crystals, infrared spectroscopy was performed on them. The product was mixed with KBr at a mass ratio of 1:100 and ground or pressed into blocks. The raw material hexamethylenetetramine and the product were measured by infrared spectrometer at 4000-500cm -1 Tested within the range, the results are as follows Figure 2 and Figure 3 As shown. Through analysis, it can be found that the wavelength is 1000cm -1 The absorption peak near the graph is the CN stretching vibration absorption peak in hexamethylenetetramine. According to the analysis of the absorption peaks in the figure, it can be inferred that the purple crystal is the target product [C6H 12 N4][CH2O][K(H2O)]{[β-Mo8O26 ] 0.5}.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 3 is that the molar ratio of the raw materials hexamethylenetetramine, KSCN and (NH4)2MoO4 is adjusted to 1:1:1, and the other implementation conditions are the same as those in Example 3. As a result, the bottom of the cup was evaporated to dryness and no hexamethylenetetramine crystalline material was obtained.
[0060] Comparative Example 2
[0061] The difference between this comparative example and Example 3 is that the molar ratio of the raw materials hexamethylenetetramine, KSCN and (NH4)2MoO4 is adjusted to 1:2:1, and the other implementation conditions are the same as Example 3. As a result, there is precipitation at the bottom of the cup and no hexamethylenetetramine crystalline material can be obtained.
[0062] Comparative Example 3
[0063] The difference between this comparative example and Example 3 is that the molar ratio of the raw materials hexamethylenetetramine, KSCN and (NH4)2MoO4 is adjusted to 1:3:1, and the other implementation conditions are the same as those of Example 3. As a result, crystals are produced, but no infrared peak is detected, so the target product [C6H 12 N4][CH2O][K(H2O)]{[β-Mo8O 26 ] 0.5}.
[0064] Experimental example
[0065] The following experiment was conducted using the hexamethylenetetramine crystalline material prepared in Example 4 as an example.
[0066] 1. X-ray powder diffraction
[0067] In order to detect the sample purity of hexamethylenetetramine crystal materials, 20 mg of single crystals were selected and ground into powder. The powder X-ray diffractometer was used for testing at room temperature. The 2θ angle was set in the range of 5-50°. The experimental analysis data structure is as follows: Figure 4 As shown, the black curve represents the actual value and the red curve represents the simulated value. By comparing the diffraction peaks of the two curves, it can be found that the peak positions of the two curves in the actual measurement and theoretical simulation are almost consistent, indicating that the hexamethylenetetramine crystalline material is a single pure phase, laying the foundation for subsequent performance testing and research.
[0068] 2. Single crystal X-ray diffraction test
[0069] A transparent single crystal (0.12 mm × 0.10 mm × 0.08 mm) with no impurities on the surface and suitable size was selected and placed on a Bruker SMART APEXⅡ single crystal X-ray diffractometer. Mo-Kα radiation (λ = 0.071073 nm) monochromatized with graphite was used as the diffraction light source. The diffraction data of the sample were collected at low temperature (100 K) and room temperature (293 K). The crystal structure was solved by direct method using the SHELXL-97 program, and the F-based 2 The full matrix method was used for refinement, and non-hydrogen atoms were anisotropically corrected. The specific unit cell parameters are shown in Table 1.
[0070] Table 1 Single crystal X-ray diffraction data of hexamethylenetetramine crystalline materials
[0071]
[0072]
[0073]
[0074] like Figure 5 and Figure 6 As shown, the molecular formula of hexamethylenetetramine crystalline materials is C7H 16 KMo4N4O 15 The low-temperature and room-temperature space groups are all triclinic, and they are centrosymmetric P-1 space groups. The simplest asymmetric unit of hexamethylenetetramine crystal materials contains two molecules of hexamethylenetetramine, one molecule of molybdenum oxide isopoly acid, and two molecules of crystal water. Under certain conditions, the isopoly acid reduces the activation energy of the reaction, so that it induces hexamethylenetetramine to synthesize under the action of hydrochloric acid and undergoes a catalytic reaction to generate CH2O, which promotes the reaction of CO2 to form aldehydes, thereby achieving the purpose of carbon fixation.
[0075] The arrangement of anions and cations in the spatial structure will directly affect the physical properties of the material. Figure 7 and Figure 8 It can be seen that at 100K, the structural units of hexamethylenetetramine crystalline materials in the ac plane are connected to each other through K···O forces, and the hexamethylenetetramine is suspended in it like a "lantern", extending infinitely along the b axis to form a one-dimensional chain structure. In order to further explore the structural changes that may be caused by the molecular arrangement in hexamethylenetetramine crystalline materials, three adjacent hexamethylenetetramine and molybdic acid structures were selected in the ac plane, and the spatial distance between the C5···Mo4 in them was compared at different temperatures. The results show that as the temperature increases, the distance increases from low temperature to Increase to The distance from low temperature to room temperature increases The increase in temperature will cause the chain structure along the a-axis to expand and contract, thus affecting the change in the electrical properties of the material. In the ab plane, the structural units are also connected to each other through the K···O force and extend infinitely toward the a-axis, thus forming Figure 8 The one-dimensional chain structure shown.
[0076] In the ab plane, each structural unit of the hexamethylenetetramine crystal material extends infinitely toward the a-axis and the b-axis through the interaction of K···O bonds, and finally forms Fig. 9 The two-dimensional network structure shown in Figure 1 is a 3D structure. The two-dimensional network organic-inorganic hybrid layer is assembled into a three-dimensional structure in space through hydrogen bonding interactions in the bc plane along the c axis direction through NH···O interactions ( Fig.10 ).
[0077] 3. Thermogravimetric analysis
[0078] Under nitrogen protection, the heating rate was set to 10K / min, and the hexamethylenetetramine crystal material was subjected to thermogravimetric analysis when the temperature was raised from room temperature to 320-850K. The results are as follows: Fig.11 As shown. Analysis shows that the decomposition of hexamethylenetetramine crystalline materials is divided into four stages: the first stage is at a temperature of 320-480K, with a weight loss rate of 0.02%, and it is speculated that the compound loses one molecule of crystal water (theoretical weight loss rate is 0.02%); the second stage is at a temperature of 480-520K, with a weight loss rate of 7.4%, which is basically consistent with the theoretical weight loss rate of 8.2% of one-third of hexamethylenetetramine, and a strong endothermic peak appears synchronously on the DTA curve; the third stage is at a temperature of 520-850K, with a weight loss rate of 19.3%, which is basically consistent with the theoretical weight loss rate of 16.4% of the remaining two-thirds of hexamethylenetetramine. At this time, the compound stops decomposing and the weight loss rate no longer changes; the last remaining stable residual compound is speculated to be the residue left by the incomplete decomposition of the remaining ammonium molybdate molecules. The thermogravimetric test results are consistent with the crystal structure data of hexamethylenetetramine crystalline materials, indicating that hexamethylenetetramine crystalline materials have good thermal stability.
[0079] 4. Hirshfeld surface analysis
[0080] In order to further determine the structural differences in the interactions between molecules in hexamethylenetetramine crystal materials, the interactions between atoms in the crystal structure were calculated and analyzed using the crystalexplorer software and the DFT principle. The atoms of the hexamethylenetetramine and ammonium molybdate complex were selected for modeling, and then the Hirshfeld surface was imaged along the 2D fingerprint map using the normalized atomic interaction (dnorm) as a parameter to obtain an overview of the interaction forces between different atoms. Fig.12As shown in Figure 1, the Hirshfeld surface contains one molecule of hexamethylenetetramine. The interactions are then quantified using fingerprints, such as Figure 13-Figure 20 As shown, through the fingerprint map, we can see that the interaction between H···H accounts for 30% of the entire crystal, the interaction between H···O accounts for 51.9% of the entire crystal, the interaction between N···H and H···N accounts for 15.2% of the entire crystal, the interaction between N···C accounts for 2.3% of the whole, the interaction between C···C and H···C accounts for 0.4% of the whole, and the interaction between N···O accounts for 0.1% of the whole; therefore, it shows that there is a strong hydrogen bond interaction force between the molecules of hexamethylenetetramine crystal materials, and this result is consistent with the result of crystal structure analysis that there is a three-dimensional hydrogen bond structure in the complex.
[0081] 5. Cyclic Voltammetry
[0082] In order to study the electrochemical properties of hexamethylenetetramine crystalline materials, the electrode was first made. The test sample and graphite were mixed and ground at a mass ratio of 1:5 to make the corresponding working electrode; then the three-electrode system (glassy carbon electrode, auxiliary electrode, reference electrode) was used to test in a mixed solution of 0.1M H2SO4 and 0.5M Na2SO4 on a CHI700E electrochemical workstation. The cyclic voltammetry results are shown in Fig.21 As shown in the figure, the oxidation peak current ipa and reduction peak current ipc, the oxidation peak potential Epa and reduction peak potential Epc are shown respectively. The black curve represents the cyclic voltammetry curve of the hexamethylenetetramine crystal material at a scan rate of 0.1V / s, and the red curve represents the cyclic voltammetry curve of the hexamethylenetetramine crystal material at a scan rate of 0.2V / s. The test results show that there is a pair of obvious reversible redox peaks in the potential range of 0.5 to 1.2V. When the scan rate is 0.1V / s, its half-peak potential E 1 / 2 0.932V(E 1 / 2 =(Epa+Epc) / 2, where Epa is the oxidation peak potential and Epc is the reduction peak potential); when the scan rate is 0.2 V / s, E 1 / 2 When the scanning rate is less than 0.5 V / S, the double layer capacitance Cd does not change with the scanning rate and the current increases linearly with the scanning rate. In the potential interval E, the amount of electricity required to form or remove the adsorption film can be easily measured. The introduction of -OH groups into ammonium molybdate and hexamethylenetetramine respectively greatly improves the Mo 6+ / Mo 4+ The reversibility of redox indicates that hexamethylenetetramine-based crystal materials have good electrochemical properties and are new organic-inorganic crystal materials with electron transfer capabilities.
Claims
1. A hexamethylenetetramine crystalline material, characterized in that: The chemical formula of the crystalline material is [C6H 12 N4][CH2O][K(H2O)]{[β-Mo8O 26 ] 0.5 }, the crystal material belongs to the triclinic system, the space group is P-1, and the unit cell parameters are α=97.344(10)°, β=101.117(9)°, γ=108.658(11)°, 2. The method for preparing the hexamethylenetetramine crystalline material according to claim 1, characterized in that: The method comprises the following steps: crystallizing hexamethylenetetramine, cyanide and molybdenum oxide isopoly acid through evaporation reaction of aqueous solution to obtain hexamethylenetetramine crystal material.
3. The method for preparing hexamethylenetetramine crystalline material according to claim 2, characterized in that: The method comprises the following steps: dissolving hexamethylenetetramine, cyanide and molybdenum oxyisopoly acid respectively, then mixing them, and allowing the mixed solution to react for 6-8 days to obtain a hexamethylenetetramine crystal material; the molar ratio of the hexamethylenetetramine, cyanide and molybdenum oxyisopoly acid is 1.3-1.5:5.5-5.8:1-1.
5.
4. The method for preparing the hexamethylenetetramine crystalline material according to claim 2 or 3, characterized in that: The cyanide is potassium thiocyanide or potassium cyanate; the molybdenum oxyisopoly acid is ammonium molybdate or sodium molybdate.
5. The method for preparing hexamethylenetetramine crystalline material according to claim 3, characterized in that: First, hexamethylenetetramine and cyanide are dissolved separately and then mixed to obtain a premixed solution. The premixed solution is then added to the molybdenum oxide isopoly acid solution and mixed evenly to obtain a mixed solution.
6. The method for preparing hexamethylenetetramine crystalline material according to claim 5, characterized in that: The pH value of the molybdenum oxyisopoly acid solution is 1-1.
5.
7. The method for preparing hexamethylenetetramine crystalline material according to claim 6, characterized in that: The reagent for adjusting the pH value is a hydrochloric acid, sulfuric acid or nitric acid solution with a concentration of 30-40wt%.
8. The method for preparing hexamethylenetetramine crystalline material according to claim 3, characterized in that: The static reaction time is 7 days.
9. The method for preparing hexamethylenetetramine crystalline material according to claim 3, characterized in that: The molar ratio of hexamethylenetetramine, cyanide and molybdenum oxide isopoly acid is 1.42:5.55:1.02.
Citation Information
Patent Citations
Copper iodine complex of hexamethylene tetramine ligand, preparation method and application thereof
CN109384804A
Manganese-based pyridine fluorescent crystal material, preparation method and application
CN116083075A
Molybdenum-doped anti-perovskite nitride three-dimensional self-supporting material and preparation method and application thereof
CN116470074A
Three-dimensional supramolecular structure phosphorus molybdenum oxygen cluster crystal material and preparation method thereof
CN118852015A